The Legal Due to the Naming of Street Light Taxes on Regional Taxes & Retribution - Ceisar Eben Ezer Purba (Jurnal Daulat Hukum, 2022)
The study describes the problem with the naming of Street Lighting Tax in Act No. 28 of 2009 which he practiced often led to multiple interpretations from the community, which then the community assumed that by paying a tax on the use or utilization of electricity, the people asked for a return in the form of providing public street lighting facilities around their settlements. Of course, the naming of Street Lighting Tax clearly raises problems and polemics that are still ongoing in the community, so it is necessary to get attention from the Government so that the naming of Street Lighting Tax can be placed in the right and correct position. The purpose of this research is more directed to determine the impact or legal consequences that occur on the naming of Street Lighting Tax in Act Number 28 of 2009. This normative legal research uses two problem approaches, namely the statute approach and the comparative approach. The conclusion in this study explains that the provisions of Article 1 number 28 jo. Article 52 of Act No. 28 of 2009 clearly results in obscure legal norms. So that the nomenclature or naming of Street Lighting Tax is a wrong thing if then the public is only asked to pay taxes on the use of electricity but then the public does not get in return for public street lighting facilities. So if it is compared in other countries such as Malaysia which uses the name Service Tax, in Germany it uses the name Electricity Tax which both provides returns in the form of service quality and electricity savings and control of environmental issues, while in the United States it uses the name Carbon Tax imbalance. It is closely related to the fuel that causes climate decline in the country. So that from this comparison there should be a change in the nomenclature of the Street Lighting Tax which in society often arises multiple interpretations.